Electronic module as learning needs to write exposition texts for junior high school students - Charlina Charlina; Elvrin Septyanti; Tria Putri Mustika; Annisa Rahmi (Journal of Education and Learning (EduLearn), 2022)
This study was a step toward the creation of an e-module to creat flips book-based exposition texts for junior high schools. The purpose of this study was to offer an examination of students' demands when creating exposition papers. A survey was used for the investigation. The data for this inquiry was gathered through a questionnaire. In this study, a Likert scale was utilized to examine students' attitudes, opinions, and perceptions of the built electronic module. This research made use of a checklist-style questionnaire with a range of assessments of 1 to 5. The questionnaire was distributed to students from four junior high schools. This sampling technique was based on the sampling quota established by the researcher. The data analysis technique involved converting the category value into an assessment score and examining the result. According to the findings, 61.5% of students had difficulties in interpreting the material of exposition text, and the rest of 80.1% desired that the exposition text writing content be presented using entertaining, interactive, and innovative learning methods. This showed the need for the preparation of electronic modules for writing flip book-based exposition texts.